2019
DOI: 10.22363/2312-797x-2019-14-1-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beta-Aminobutyric Acid on Activity of Peroxidase and Polyphenol Oxidase Enzymes in Cucumber Infected With Nematode Meloidogyne Javanica

Abstract: Beta-amino-butyric acid is introduced as an inducer of resistance in plants against plant pathogens. In this research, the induction of some defensive compounds including peroxidase and polyphenol oxidase enzymes by this compound against the rootstock node-producing nematode Meloidogyne javanica in cucumber was investigated. The results showed that inoculation of cucumber roots infected with root-knot nematode with the chemical composition of BABA from the first day after inoculation increased the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, both peroxidase and polyphenol oxidase activities reached their highest peak after 5 dpt, with superiority over both controls. Peroxidase and polyphenol oxidase are related to plant defense against a wide range of plant pathogenic microorganisms [73]. Recently, it was reported that foliar application of phenolic acids on tomato plants raised the activities of phenylalanine ammonia-lyase and polyphenol oxidase [69].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, both peroxidase and polyphenol oxidase activities reached their highest peak after 5 dpt, with superiority over both controls. Peroxidase and polyphenol oxidase are related to plant defense against a wide range of plant pathogenic microorganisms [73]. Recently, it was reported that foliar application of phenolic acids on tomato plants raised the activities of phenylalanine ammonia-lyase and polyphenol oxidase [69].…”
Section: Discussionmentioning
confidence: 99%
“…second larvae of nematode is more common. Extracting egg and providing second larvae was done using [4] method.…”
Section: Introductionmentioning
confidence: 99%